Caracterização termo-mecânica de interconectores metálicos recobertos com filmes de LaCrO3 - Sousa, Cláwsio Rogério Cruz de (2010)
The cells unitaria of the solid oxide fuel cell are separated by means of interconnects, which serve as electrical contact between the cells. Lanthanum Chromite (LaCrO3) has been the most common material used as interconnect in solid oxide fuel cells. Reducing the operating temperature around 800 º C of cells to solid oxide fuel make possibilite the use of metallic interconnects as an alternative to ceramic LaCrO3. Metallic interconnects have advantages over ceramic interconnects such as high thermal conductivity, electricity, good ductility, low cost, good physical and mechanical properties. In this work evaluate the thermo-mechanical properties of the metallic substrate and coated metallic substrate with the ceramic LaCrO3 film via spray-pyrolysis, in order to demonstrate the feasibility of using this material as a component of a fuel cell solid oxide. The materials were characterized by X-ray diffraction, oxidation behavior, mechanical strength, optical microscopy (OM) and scanning electron microscopy (SEM). The X-ray diffraction proved the formation phase of the LaCrO3 on the metallic substrate and the identification of the phases formed after the oxidative test and mechanical strength at high temperature. The oxidation behavior showed the increased oxidation resistance of the coated metallic substrate. It was noted that the mechanical resistance to bending of the coated metallic substrate only increases at room temperature. The optical microscopy (OM) has provided an assessment of both the metallic substrate and the LaCrO3 film deposited on the metal substrate that, in comparison with the micrographs obtained from SEM. The SEM one proved the formation of Cr2O3 layer on the metallic substrate and stability of LaCrO3 film after oxidative test, it can also observe the displacement of the ceramic LaCrO3 film after of mechanical testing and mapping of the main elements as chromium, manganese, oxygen, lanthanum in samples after the thermo-mechanical tests.